PENGARUH PEMBERIAN BOKASHI DAUN GAMAL (Gliricidia sepium) DAN DIAMETER AGREGAT TANAH TERHADAP PERUBAHAN SIFAT FISIKA TANAH DAN PERTUMBUHAN AWAL TANAMAN TOMAT (Lycopersicum esculentum Mill.) PADA ENTISOLS SIDERA - Zaitun Zaitun; Uswah Hasanah; Abd. Rahman (Agroland: Jurnal Ilmu-ilmu Pertanian, 2013)
Soil is a growing media for plant and living environment for soil micro dan macro organisms. Low soil fertility can become a limiting factor for plant growth and productivity. Soil fertility can be improved by adding organic materials such as bokashi.Another factor than can affect plant growth is soil aggregate diameter through its influence on various soil physical characteristics. The research objective was to determine the effect of gamal leaf bokashi (Gliricidia sepium)        and soil aggregate diameteron soil physical characteristics and early growth of tomato plant (Lycopersicum esculentum Mill.) in Entisols Sidera. The research was conducted from November to Desember 2013. Composite soil samples from 0-20 cm were taken from Sidera village Biromaru Sub District of Sigi District. The soil was sieved to obtain various aggregate diameter including       < 2 mm, 2-4 mm and 4-6 mm.The bokashi of gamal leaf was applied to the different soil aggregate diameter at a rate of 0, 30 t ha-1, 60 t ha-1. The research results showed no interaction effect of bokashi and soil aggregate diameter. The bokashi significantly reduced the bulk density to only 1,06 g cm-3 in 60 t ha-1 bokashi treatment. In contrast, the soil permeability significantly increased up to 26,18 cm h-1 and the water content at field capacity up to 22,02%. Shoot dry weight under 30 t ha-1 bokashi application was significantly higher than that under no bokashi added and that under 60 t ha-1 bokashi. Similar trend was also showed by dry root weight and total root length. Soil bulk density and water content at field capacity significantly and consistently reduced with larger soil aggregate diameter while soil permeability increased. Highest plant dry weight and total root length was found in 2-4 mm soil aggregate diameter treatment.                                                                                                                               Key Words : Aggregate diameter, bokashi, soil physical characteristics, and tomato growth.